Familial Undercurrents : Untold Stories of Love and Marriage in Modern Iran - Najmabadi, Afsaneh, 1946- (Book collections on Project MUSE., 2022)
"Afsaneh Najmabadi draws on her family history to tell a larger story of the transformations of notions of love, marriage, and family life in mid-twentieth-century Iran."--